Sequence isomerism-dependent self-assembly of glycopeptide mimetics with switchable antibiofilm properties. Issue 35 (23rd July 2019) - Chen, Limin; Feng, Jie; Yang, Dan; Tian, Falin; Ye, Xiaomin; Qian, Qiuping; Wei, Shuai; Zhou, Yunlong
Abstract : We report sequence isomerism-dependent and reversible self-assembly behaviors of glycopeptide mimetics in response to different stimuli. Based on the glycopeptide mimetic assemblies, reversible ON/OFF switching of biofilm disruption was achieved. Abstract : In biological systems, diverse amino acid sequences and functional decorations endow proteins with specific functions. Functionally modified oligopeptides are attractive building blocks to assemble stimuli-responsive biomimetic superstructures for mimicking soft structures in nature and biomaterial applications. In this work, we selectively synthesized the structurally simplest isomeric tripeptides ( i.e., Ala–Gly–Gly–OH, Gly–Ala–Gly–OH and Gly–Gly–Ala–OH) to demonstrate how the subtlest change in sequence isomerism influences the self-assembly of glycopeptides. To impart self-assembly capability and stimuli-responsiveness, the isomeric tripeptides were modified with a hydrophobic n -butylazobenzene tail at the N-terminal. We observed three different self-assembled 1-D morphologies ( i.e., nanotwists, nanoribbons and nanofibers) from the azobenzene-glycopeptides (AGP s) under the same conditions when the position of the Ala residue was switched. Experimental methods including transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy and circular dichroism (CD) spectroscopy were used to characterize the structural details of glycopeptide mimetic assemblies. Martini coarse-grained molecular dynamics (MD) simulations confirmed such structural observations and investigated the differences in assembly mechanisms. Furthermore, the glycopeptide mimetic assemblies showed a reversible disassembly–assembly process in response to temperature, light or host–guest chemistry, and can be used as switchable antibiofilm nanoagents.